The Degree of Using Infographics in Presenting & Presenting data in Public Education Agency Programs from General Supervisors’ Perspective in the Ministry of Education in The Kingdom of Saudi Arabia - Al-Razouq, Wardah Ali Hassan; Al-Shehri, Ajlan Mohammed Houjeer (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed at identifying the degree of using infographics in presenting data in the programs of the Public Education Agency, the most important obstacles to its use, and making development proposals from the point of view of the general supervisors of the Saudi Ministry of Education, The study used the descriptive approach and relied on the questionnaire as a tool for gathering the required information for this study, The researcher used the comprehensive inventory method and applied the study tool to the entire community consisted of (230) male and female general supervisors, The results of the study found that the study sample individuals agreed to the use of infographics in presenting data in the Agency’s programs, with an arithmetic average of (3.70), The results showed that the study sample individuals agreed that there are obstacles to the use of infographics in the Agency, with an arithmetic average of (4.08), The most significant obstacles were the lack of training programs for the Agency staff in production infographics field of all kinds, The inability to download design programs because of the security programs on desktop of Agency staff, The results indicated that the most important proposals that could contribute to the development of the Agency’s infographics use are: Conducting training courses for the general supervisors to develop their skills in using infographics, preparing a guidebook to help.